Niacin mitigates heat stress-induced reduction in performance of Taihe black-boned silky fowl through modulation of gut microorganisms and short-chain fatty acids - Mei, Wenliang; Chen, Chuanbin; Gao, Xiaona; Zhang, Wenyan; Hu, Ziyu; Qu, Mingren; Wan, Gen; Xu, Lanjiao (Frontiers in Veterinary Science, 2025)
This study aimed to evaluate the dose-dependent effects of nicotinic acid (NA) on growth performance, cecal short-chain fatty acid (SCFA) profiles, and gut microbiome composition in Taihe black-boned silky fowl (TBsf) under heat stress (HS) conditions. In the experiment, 150 healthy male TBsf were selected and randomly assigned to five treatment groups, with 30 individuals per group. The HS groups were fed a basal diet supplemented with 0, 200, 400, and 800 mg/kg of NA, respectively. HS significantly elevated body temperature and serum heat shock protein 70 (HSP70) concentration compared with the control group (thermal neutral, TN) (p < 0.05), while reducing the growth performance and apparent digestibility of crude protein in TBsf (p < 0.05). The addition of 800 mg/kg NA to the diet significantly reduced body temperature. Compared with the HS group, the incorporation of 200–800 mg/kg NA significantly decreased serum HSP70 levels, significantly increased the average daily gain (ADG) of TBsf, and significantly decreased the feed-to-gain ratio (F/G) (p < 0.05). Cecal microbial analysis showed that, compared with the TN group, the abundance of Merdimonas, Proteobacteria, and Galbibacter significantly increased (p < 0.05), while the abundance of Bacteroides, Prevotella, and Parasutterella significantly declined (p < 0.05). Furthermore, the NA-supplemented group exhibited a significant rise in the enrichment of Olivibacter and Flintibacter (p < 0.05) and a marked reduction in the enrichment of Proteobacteria (p < 0.05). Additionally, the addition of NA significantly elevated the levels of acetic acid, butyrate, and propionic acid in the cecum (p < 0.05). In conclusion, dietary NA supplementation mitigated the adverse effects of HS on TBsf, primarily by enriching beneficial microbiota such as Bacteroides and Flintibacter, and promoting the production of SCFAs like butyric acid and acetic acid.